Experiences of living with juvenile idiopathic arthritis: a qualitative systematic review protocol. Issue 9 (8th September 2020) - Min, Ming; Hancock, David G.; Aromataris, Edoardo; Crotti, Tania; Boros, Christina
ABSTRACT: Objective: The objective of this review is to identify, critically appraise and synthesize the available qualitative evidence to understand the experiences of children, young adults and their carers living with juvenile idiopathic arthritis in any setting. Introduction: Juvenile idiopathic arthritis is the most common rheumatic disease in childhood. Despite the availability of effective treatments, the disease still has negative impacts on patients' and carers' lives. Patients' and carers' experiences of living with juvenile idiopathic arthritis have been recognized as important in the measurement of health status and treatment implementation. Addressing these needs will facilitate more effective management and treatment of the disease. This protocol describes a method for a systematic review regarding the perspectives from patients and carers in order to highlight the needs of families throughout their juvenile idiopathic arthritis journey. Inclusion criteria: Studies on the experiences of patients aged <21 years who have been diagnosed with juvenile idiopathic arthritis according to the International League of Associations for Rheumatology criteria, as well as the experiences of their carers, will be considered. Papers included in this review will include, but not be limited to, designs such as phenomenology, grounded theory and ethnography. Methods: A comprehensive search using PubMed, CINAHL, Embase, PsycINFO and Web of Science was undertaken in August 2019. Available studies published in English from 2001 to 2019 will be included. The recommended JBI method for study selection, critical appraisal, data extraction and data synthesis will be used. Systematic review registration number: PROSPERO (CRD42019133165).